2017
DOI: 10.1007/s00424-017-2052-5
|View full text |Cite
|
Sign up to set email alerts
|

How does the stimulus define exocytosis in adrenal chromaffin cells?

Abstract: The extent and type of hormones and active peptides secreted by the chromaffin cells of the adrenal medulla have to be adjusted to physiological requirements. The chromaffin cell secretory activity is controlled by the splanchnic nerve firing frequency, which goes from approximately 0.5 Hz in basal conditions to more than 15 Hz in stress. Thus, these neuroendocrine cells maintain a tonic release of catecholamines under resting conditions, massively discharge intravesicular transmitters in response to stress, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 151 publications
0
18
0
Order By: Relevance
“…In recent years, considerable progress has been made in unravelling the complex molecular background and the functional elements of the highly regulated exocytotic machinery in adrenomedullary chromaffin cells (Figure 2) [145,171,172]. Release of acetylcholine by the splanchnic nerve activates the nicotinic receptor on chromaffin cells, resulting in opening of the ionophoric part of the receptor protein, thereby allowing the entry of extracellular sodium (Na + ) and calcium (Ca 2+ ).…”
Section: Adrenomedullary Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, considerable progress has been made in unravelling the complex molecular background and the functional elements of the highly regulated exocytotic machinery in adrenomedullary chromaffin cells (Figure 2) [145,171,172]. Release of acetylcholine by the splanchnic nerve activates the nicotinic receptor on chromaffin cells, resulting in opening of the ionophoric part of the receptor protein, thereby allowing the entry of extracellular sodium (Na + ) and calcium (Ca 2+ ).…”
Section: Adrenomedullary Functionmentioning
confidence: 99%
“…The distribution of the different calcium channel subtypes is species specific. The P/Q-type calcium channel predominates in human adrenomedullary chromaffin cells [167,171,172]. As a consequence of elevated intracellular Ca 2+ concentrations, the exocytotic machinery and the regulatory components for vesicular exocytosis are activated, which occurs through a pathway consisting of secretory vesicle recruitment, docking, priming, and fusion with the plasma membrane.…”
Section: Adrenomedullary Functionmentioning
confidence: 99%
“…Under basal conditions, exocytosis from the chromaffin cells is a strictly controlled process that largely depends on calcium uptake [50][51][52][53]. However, it can be further enhanced by additional stimuli, including hypoglycaemia, hypotension, hypoxemia and emotional distress [4,17,53,54]. Interestingly, it has been recently reported that EPO Tg6 mice are strongly hypoglycaemic and that low BGL correlates with the degree of erythropoiesis [22,55].…”
Section: Discussionmentioning
confidence: 99%
“…Chromaffin cells from the adrenal medulla are electrically excitable cells that release catecholamines and neuropeptides in response to stress. They are equipped with a set of ion channels that control membrane excitability, Ca 2+ influx signals, and consequently the secretory response (Marengo and Cárdenas, ). Since these neuroendocrine cells need to respond to a wide range of physiological situations, from maintaining a tonic release under basal conditions to a massive release of transmitters in response to stress, a tight regulation of the membrane excitability and Ca 2+ signals is required.…”
Section: Discussionmentioning
confidence: 99%
“…Chromaffin cells from the adrenal medulla are electrically excitable cells that release catecholamines and neuropeptides in response to stress. They are equipped with a set of ion channels that control membrane excitability, Ca 2+ influx signals, and consequently the secretory response (Marengo and C ardenas, 2018). Since these neuroendocrine cells need Fig.…”
Section: Discussionmentioning
confidence: 99%